2017
DOI: 10.1051/0004-6361/201731948
|View full text |Cite
|
Sign up to set email alerts
|

Are some CEMP-s stars the daughters of spinstars?

Abstract: Carbon-enhanced metal-poor (CEMP)-s stars are long-lived low-mass stars with a very low iron content as well as overabundances of carbon and s-elements. Their peculiar chemical pattern is often explained by pollution from an asymptotic giant branch (AGB) star companion. Recent observations have shown that most CEMP-s stars are in binary systems, providing support to the AGB companion scenario. A few CEMP-s stars, however, appear to be single. We inspect four apparently single CEMP-s stars and discuss the possi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 47 publications
1
44
0
Order By: Relevance
“…5 we show [Sr/Ba] vs. relative C and O abundances compared to generalised FRMS yields (Frischknecht et al 2012) with an average of [Sr/Ba] ∼ 0.5 and AGB yields ([Sr/Ba] ∼ −0.5 from predictions of metal-poor AGB stars with 1.5-2 M ; Cristallo et al 2011). The bottom panel of the same figure shows the separation of FRMS using O predictions from Choplin et al (2017), contrasting with the above described AGB yields. Despite some of the stars falling slightly off the predictions, there is an overall good agreement between the results illustrated by the two panels.…”
Section: Abundance Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…5 we show [Sr/Ba] vs. relative C and O abundances compared to generalised FRMS yields (Frischknecht et al 2012) with an average of [Sr/Ba] ∼ 0.5 and AGB yields ([Sr/Ba] ∼ −0.5 from predictions of metal-poor AGB stars with 1.5-2 M ; Cristallo et al 2011). The bottom panel of the same figure shows the separation of FRMS using O predictions from Choplin et al (2017), contrasting with the above described AGB yields. Despite some of the stars falling slightly off the predictions, there is an overall good agreement between the results illustrated by the two panels.…”
Section: Abundance Resultsmentioning
confidence: 98%
“…The Sr/Ba ratio is different in AGB stars and FRMS, which makes Sr/Ba an efficient and useful descriptor to trace possible formation sources, in the sense that only two elements/absorption features need to be analysed to derive this abundance ratio. Additionally, Choplin et al (2017) showed that the Sr/Ba ratio, together with the O production in FRMS, is much higher than in AGB stars.…”
Section: Abundance Resultsmentioning
confidence: 99%
“…We note that in Figure 8 the single CEMP-s stars seem to be preferentially located on the lower side of the A(C) distribution of the CEMP-s stars. Choplin et al (2017) model the abundances of the single CEMP-s stars with massive spinstar models, and succeed for three out of the four modelled stars. Spinstar models are also employed to explain the abundances of CEMP-no stars (e.g.…”
Section: A High Fraction Of Binaries Among Intermediate/high Carbon Bmentioning
confidence: 94%
“…Photometric and spectroscopic bservations of the electromagnetic counterpart (AT 2017gfo;Cowperthwaite et al 2017;Drout et al 2017;Kilpatrick et al 2017;Shappee et al 2017) of the recent LIGO/VIRGO detection of a binary neutron star merger in 2017 (GW170817; Abbott et al 2017a,b) provided direct evidence of main r-process element production. An additional source, operation of an s-process in spinstars, has been recently suggested (Frischknecht et al 2012;Cescutti et al 2013;Frischknecht et al 2016;Choplin et al 2017Choplin et al , 2018, which could also possibly produce Ba. Following these, the dominant site for Ba (along with carbon) production transitions to low-to intermediatemass thermally pulsating AGB stars, where the main s-process operates.…”
Section: The Origin and Evolution Of Carbon Iron And Bariummentioning
confidence: 99%